Opression - Graeber, David (Cadernos de Campo (São Paulo, 1991), 2023)
The linguistic connections between the word "oppression" and the sensation of being "pressed down, crushed by a heavyweight" that exists in almost every language points to a reflection on the political dilemmas born out of cultural relativism.